Breastfeeding support as predictors of sustainable breastfeeding practices of nursing mothers with common mental disorders in tertiary hospital nurseries in Nigeria: a cross sectional study - Michael Abel Alao; Olayinka Rasheed Ibrahim; Sakiru Abiodun Yekinni; Sikirat Adetoun Sotimehin; Udochukwu Michael Diala; Datonye Christopher Briggs; Aishatu Zaidu Musa; Zainab Oluwatosin Imam; Esther Oluwatoyin Famutimi; Adedeji Abiodun Idris; Adaeze C. Ayuk; Kenechukwu Kosisochukwu Iloh; et al. (BMC Pregnancy and Childbirth)
Abstract Background The postpartum period is associated with an increased risk of maternal mental disorders. The combined effect of having the mother's infant admitted to a tertiary hospital in a low-resource setting and the need to exclusively breastfeed the infant may exaggerate this risk. This study aimed to determine the breastfeeding support provided to mothers whose infants were hospitalised in Nigerian tertiary hospital nurseries and the prevalence of common mental health disorders among this population. Methods This was a national cross-sectional study involving mothers of hospitalised infants from eleven Nigerian tertiary hospitals between May and August 2022. To assess mothers' mental health and breastfeeding support, we utilised the WHO self-reporting Questionnaire 20 and an adapted WHO/UNICEF ten-step breastfeeding support package. Results Of the 1,120 mothers recruited from neonatal nurseries in the six geopolitical zones in Nigeria, only 895 had a complete dataset for analysis. The mean age of the mothers was 29.9 ± 6.2; with 54.7% belonging to the low-socioeconomic class. Most of the mothers (835, 93.3%) received antenatal care, and 591: 66.0% were delivered at term. Overall, less than half (427; 47.7%) of the mother received optimal breastfeeding support. One in every four, 216; 24.0% of nursing mothers (95% CI: 21.235 to 26.937%) had common mental disorders (CMD). Pre-pregnant mental health disorders were reported in 41; 4.6% of the nursing mothers. Overall, the lowest performing areas of breastfeeding support were family-centred care (198, 22.1%), practical skill demonstration in the ward (n = 279, 31.2%), and antenatal clinics (n = 294, 32.8%). CMDs were significantly associated with the healthcare provider's practical breastfeeding skill demonstration and the provision of storage facilities for breastmilk and family-centered-care. Across Nigeria's six geopolitical zones, there was an inverse relationship between optimal breastfeeding support and the proportion of mothers with CMDs. The northern zone provided better breastfeeding support and had fewer CMDs than the southern region of the country. Conclusion Common mental disorders are prevalent among nursing mothers in Nigerian tertiary hospital nurseries, and they are inversely related to breastfeeding support. Urgently required in tertiary hospitals for improved and sustainable breastfeeding practices are a focus on family-centred care and enhanced health workers’ practical breastfeeding support skills.